PENGARUH KONTEKS KELEMBAGAAN DALAM PENERAPAN REKAYASA NILAI PADA PROYEK JALAN NASIONAL - Alvin Tehmono; Gede B. Suprayoga (Himpunan Pengembangan Jalan Indonesia (HPJI), 2023)
Abstract This paper aims to explore focus areas, institutional constraints, and institutional support for implementing Value Engineering for road construction projects, which include planning, design, and construction implemen-tation, at the Directorate General of Highways. Interviews were conducted to collect data and information related to institutional elements that influence the implementation of Value Engineering at the micro (individual), meso (organizational) and macro-organizational levels. The research sampling process was carried out purposi-vely, from those who had attended Value Engineering training at the Directorate General of Highways, with a minimum of introduction level and were actively involved in a number of projects that became pilots for the application of Value Engineering from 2018 to 2020. This study shows that organizational context has an influence on the application of Value Engineering within the Directorate General of Highways. This study also provides an indication that intervention is needed to overcome obstacles and encourage the effectiveness of the implementation of Value Engineering. This study also confirms that, in practice, the technical aspects of Value Engineering are not more important than the institutional aspects. Keywords: Value Engineering; road construction; institutional support; institutional aspect Abstrak Makalah ini bertujuan mengeksplorasi area fokus, kendala, dan dukungan kelembagaan dalam penerapan Rekayasa Nilai pada proyek pembangunan jalan, yang meliputi perencanaan, perancangan, dan pelaksanaan konstruksi, di Direktorat Jenderal Bina Marga. Wawancara dilakukan untuk mengumpulkan data dan informasi yang terkait dengan elemen-elemen kelembagaan yang memengaruhi penerapan Rekayasa Nilai di tingkat-tingkat mikro (individu), meso (organisasi), dan makro-organisasi. Proses pengambilan sampel penelitian dila-kukan secara purposif, kepada mereka yang telah mengikuti pelatihan Rekayasa Nilai di Direktorat Jenderal Bina Marga, dengan minimal pada jenjang pengenalan serta aktif terlibat dalam sejumlah proyek yang menjadi pilot penerapan Rekayasa Nilai pada tahun 2018 hingga tahun 2020. Studi ini menunjukkan bahwa konteks organisasi memiliki pengaruh terhadap penerapan Rekayasa Nilai di lingkungan Direktorat Jenderal Bina Marga. Studi ini juga memberikan indikasi bahwa intervensi diperlukan untuk mengatasi kendala dan mendo-rong efektivitas penerapan Rekayasa Nilai. Penelitian ini juga menegaskan bahwa, dalam penerapannya, aspek teknis Rekayasa Nilai tidak lebih penting dibandingkan dengan aspek kelembagaannya. Kata-kata kunci: Rekayasa Nilai; pembangunan jalan; dukugan kelembagaan; aspek kelembagaan